2022
DOI: 10.3390/ijms23073808
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tumor-Suppressive miR-30e-3p Targets: Involvement of SERPINE1 in the Molecular Pathogenesis of Head and Neck Squamous Cell Carcinoma

Abstract: Recently, our studies revealed that some passenger strands of microRNAs (miRNAs) were closely involved in cancer pathogenesis. Analysis of miRNA expression signatures showed that the expression of miR-30e-3p (the passenger strand of pre-miR-30e) was significantly downregulated in cancer tissues. In this study, we focused on miR-30e-3p (the passenger strand of pre-miR-30e). We addressed target genes controlled by miR-30e-3p that were closely associated with the molecular pathogenesis of head and neck squamous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Previous research has indicated that SERPINE1 plays a crucial role in controlling the origin and development of HNSCC and might be identified as critical indicators for the accurate diagnosis and prognosis of HNSCC; hence, providing prospective therapeutic targets [ 51 ]. Consistent with its relationship with a poor prognosis in HNSCC patients, SERPINE1 overexpression enhances tumor aggressiveness and metastasis to lymph nodes and the lung [ 52 ]. In addition, functional experiments targeting SERPINE1 expression have indicated that suppressing SERPINE1 expression inhibited the malignant phenotype of HNSCC cells [ 53 ].…”
Section: Discussionmentioning
confidence: 94%
“…Previous research has indicated that SERPINE1 plays a crucial role in controlling the origin and development of HNSCC and might be identified as critical indicators for the accurate diagnosis and prognosis of HNSCC; hence, providing prospective therapeutic targets [ 51 ]. Consistent with its relationship with a poor prognosis in HNSCC patients, SERPINE1 overexpression enhances tumor aggressiveness and metastasis to lymph nodes and the lung [ 52 ]. In addition, functional experiments targeting SERPINE1 expression have indicated that suppressing SERPINE1 expression inhibited the malignant phenotype of HNSCC cells [ 53 ].…”
Section: Discussionmentioning
confidence: 94%
“…The protocols used for transient transfection of miRNAs and siRNAs were described in our previous studies [ 23 , 24 , 25 , 26 ]. The miRNA precursors and siRNAs used in this report were detailed in Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…The procedures for conducting functional assays (cell proliferation, migration, and invasion assays) with HNSCC cells were described in earlier publications [ 23 , 24 , 25 , 26 ]. In brief, for proliferation assays, Sa3 or SAS cells were transferred to 96-well plates at 3.0 Ă— 10 3 cells per well.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations